Review of Risk Management and Patient Safety in the Context of Hospital Quality Management: Literature Review - Asriani Asriani; Suci Dwi Yanti; Vergina Anggraini Abrar; Nurul Fajriah Istiqomah (International Journal of Science Technology and Health, 2024)
Introduction: One of the elements of general welfare of national goals is the realization of optimal health. Therefore, quality health services will become one of the basic needs required by everyone. In improving quality and patient safety, there are risks that must be overcome to get the desired results, for this reason hospitals need to carry out risk management. Risk management is closely related to the implementation of patient safety and worker safety in hospitals and has an impact on achieving hospital quality, etc. Methods and materials: This research is a literature review based on sources from Google Scholar with the search keyword "Risk Management and Patient Safety to Improve Hospital Quality Management." A total of five articles were identified and used in this research. Articles used in the literature review are limited to 2019-2023. Research results: Risk management and patient safety depend heavily on effective communication, knowledge and good attitudes from all parties involved in the hospital. Accurate and consistent implementation of policies and procedures is an important foundation, and the use of information technology can facilitate risk reporting and analysis. Audits and evaluations need to be carried out to ensure the effectiveness of actions provided by medical and non-medical personnel in accordance with procedures.